Development of Photo Studio Reservation Website Design Using Design Thinking Method - Asty Yuliani; Ariq Cahya Wardhana (Postgraduate, University of Mataram, 2025)
This research aims to design the interface of a web-based reservation system at Infokus Photo Studio using a Design Thinking approach. Obstacles in the reservation process, such as schedule conflicts, unavailability of time slot display, and late confirmation, were identified through customer questionnaires. The Design Thinking method was applied in five stages: empathize, define, ideate, prototype, and test. The research was conducted by identifying user needs, designing ideas, creating prototypes, and conducting tests. Testing using the System Usability Scale (SUS) involved eight respondents and resulted in an average score of 87, which is classified as acceptable in the acceptability range, a B on the Value Scale, and very good on the Adjective Rating. These results show that this system design successfully simplifies the reservation process, reduces operational errors, and improves service quality and smooth studio operations.